Implications of current validity frameworks for classroom assessment - MOR, Ezgi; KARATOPRAK ERŞEN, Rabia (International Journal of Assessment Tools in Education, 2023)
The argument-based approach is the current framework for validity and validation. One of the criticisms is that understanding and applying this approach to practice are complicated and require abstract thinking. Teachers or school administrators in teaching and learning need support in their validation practice. Due to the abstract structure of validity, the test users and instructors who are not familiar with psychometrics may face problems in gathering validity evidence. Especially in classroom assessment, teachers may deal with understanding the complex methods of validation. In line with this need, the purpose of this study is to help instructors validate their assessment practices by providing a pathway to guide them through their validation processes and to make the validation process more obvious in classroom assessment. For this purpose, a checklist including the validity indicators for classroom assessment is developed. In this development process, Sireci's (2020) 4-step validation which is based on AERA et al. (2014) Standards and Bonner's (2013) study as a framework were followed. The validity indicators were composed by simplifying the AERA’s standards and the ones which are relevant to classroom assessment were selected. In addition to the standards, the aforementioned studies were investigated and the validity indicators that may be applicable in classroom assessment were determined.
Keywords: validity; argument-based approach; Measurement Theories and Applications in Education and Psychology; educational standards; L; educational assessment; Education; Eğitimde ve Psikolojide Ölçme Teorileri ve Uygulamaları; classroom assessment; Validity; Classroom assessment; Educational assessment; Argument-based approach; Educational standards; 4. Education